Mehka robotika - Erzin, Lara (Obzornik za matematiko in fiziko, 2022)
Soft robots are composed of compliant, elastic materials and offer unique applications in the fields where conventional rigid robotics cannot be applied, for instance noninvasive surgeries, prosthetics and artificial organs. Their design and operation draw heavily from nature, often mimicking the complex motion of living creatures. Due to their soft structure with the capability to change shape, soft robots are able to adapt to unpredictable environments and can safely interact with humans. The newly emerging field of soft robotics is highly multi-disciplinary, combining areas such as material physics, biomedical engineering and intelligent systems.
Keywords: mehka robotika; mehki aktuatorji; mehki materiali; senzorji